ANALISIS PENGELOLAAN LOGISTIK SUB BAGIAN PERBEKALAN UMUM DAN INVENTARIS DI RSI SURABAYA JEMURSARI - Sherly Aprillia; Agus Aan Adriansyah; Putik Novani Puspita (Jurnal Cakrawala Ilmiah, 2023)
Logistics management is the process of planning, organizing, supervising all activities including procurement, recording, distribution, storage, maintenance and disposal with the aim of making it more effective and efficient. All of these activities are interrelated with one another to provide smooth logistics services. The purpose of this study was to determine the logistics management system for the sub-section of general supplies and inventory at the Islamic Hospital of Surabaya Jemursari. This study uses a qualitative study with a case study model. Data collection techniques used were in-depth interviews, direct observation, and data documents from related units. The results and discussion of this study found problems in the process of receiving and distributing non-medical logistics goods. Other logistics management activities have been carried out properly, quickly, precisely and safely. It is hoped that the division of tasks will be even better so that service and distribution run more optimally.